2022
DOI: 10.3390/cancers14174155
|View full text |Cite
|
Sign up to set email alerts
|

HER2 in Non-Small Cell Lung Cancer: A Review of Emerging Therapies

Abstract: Human epidermal growth factor receptor 2 (HER2), a member of the ERBB family of tyrosine kinase receptors, has emerged as a therapeutic target of interest for non-small cell lung cancer (NSCLC) in recent years. Activating HER2 alterations in NSCLC include gene mutations, gene amplifications, and protein overexpression. In particular, the HER2 exon 20 mutation is now a well clinically validated biomarker. Currently, there are limited targeted therapies approved for NSCLC patients with HER2 alterations. This rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Next, we sought to challenge the barcoded ERBBprofiler assay and selected various ERBB receptor antagonists, which included approved drugs (erlotinib, gefitinib, lapatinib, osimertinib), 22 , 24 , 41 , 42 but also a failed compound (AG1478), 43 and drug candidates that are in a clinical trial stage (poziotinib, pyrotinib, TAS6417). 44 , 45 , 46 Clozapine was selected as an approved drug for targeting HTR2A. 47 As antagonist assays require activated receptors and pathways, we selected the mix of ligands to stimulate ERBB receptors and HTR2A, as well as signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we sought to challenge the barcoded ERBBprofiler assay and selected various ERBB receptor antagonists, which included approved drugs (erlotinib, gefitinib, lapatinib, osimertinib), 22 , 24 , 41 , 42 but also a failed compound (AG1478), 43 and drug candidates that are in a clinical trial stage (poziotinib, pyrotinib, TAS6417). 44 , 45 , 46 Clozapine was selected as an approved drug for targeting HTR2A. 47 As antagonist assays require activated receptors and pathways, we selected the mix of ligands to stimulate ERBB receptors and HTR2A, as well as signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, pan-HER TKIs like afatinib, neratinib, and dacomitinib have been used to treat patients with HER2-mutant NSCLC [ 71 ]. Selective HER2 tyrosine kinase inhibitors (TKIs) such as pyrotinib, poziotinib, mobocertinib, tarloxotinib, afatinib, neratinib, and dacomitinib have been employed in lung cancer treatment [ 72 ]. For instance, clinical studies have indicated that pyrotinib can enhance the overall survival of NSCLC patients with HER2 mutations, regardless of metastatic status [ 73 ].…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…Mutation in FGFR1 contributes to the promotion of mesenchymal-predominant NSCLC [ 60 ]. Additionally, Discoidin domain Receptor 2 (DDR2), a tyrosine kinase, is considered as a biomarker, as its mutation promotes tumor growth, particularly in 30% of squamous NSCLC [ 61 ]. Furthermore, the human epidermal growth factor receptor 2 (HER2), involved in activating cell proliferation pathways such as PI3K-AKT and MEK-ERK, is found in 10 to 30% of NSCLC cases, especially in adenocarcinoma [ 62 ].…”
Section: Precision Medicine and Biomarkersmentioning
confidence: 99%